Paternal Contributions to Offspring Health: Role of Sperm Small RNAs in Intergenerational Transmission of Epigenetic Information - Sharma, Upasna (Frontiers in Cell and Developmental Biology, 2019)
The most fundamental process for the perpetuation of a species is the transfer of information from parent to offspring. Although genomic DNA contributes to the majority of the inheritance, it is now clear that epigenetic information —information beyond the underlying DNA sequence— is also passed on to future generations. However, the mechanism and extent of such inheritance are not well understood. Here, I review some of the concepts, evidence, and mechanisms of intergenerational epigenetic inheritance via sperm small RNAs. Recent studies provide evidence that mature sperm are highly abundant in small non-coding RNAs. These RNAs are modulated by paternal environmental conditions and potentially delivered to the zygote at fertilization, where they can regulate early embryonic development. Intriguingly, sperm small RNA payload undergoes dramatic changes during testicular and post-testicular maturation, making the mature sperm epigenome highly unique and distinct from testicular germ cells. I explore the mechanism of sperm small RNA remodeling during post-testicular maturation in the epididymis, and the potential role of this reprogramming in intergenerational epigenetic inheritance.